FREQUENCY OF GIARDIASIS IN ACUTE AND CHRONIC DIARRHOEAL CASES - Mehmood, Tahir; Rehman, Gohar; Hayat, Muhammad (Journal of Postgraduate Medical Institute, 2011)
Objective: To determine the frequency of giardiasis in patients suffering from acute and chronic diarrhoea. Material and Methods: This descriptive study was carried out in the Department of Paediatrics, Postgraduate Medical Institute Hayatabad Medical Complex Peshawar, from Jul 2001 to Jan 2002. Stool samples from 150 patients, attending both the out patient department and admitted in unit for management, including both males and females, aged between 5 months and 12 years, with acute and chronic diarrhoea were scrutinized on three consecutive days. Results: The prevalence of giardiasis was 20% (n=15/75) in acute diarrhea and 33.3 % (n=25/75) in chronic diarrhea. Among positive cases in acute giardiasis, 80% (n=12/15) belonged to 0.5-5 years age group and 20% (n=3/15) belonged to 6-12 years age group, while in chronic giardiasis, 72% (n=18/25) belonged to 6 months-5 years age group and 28% (n=7/25) belonged to 6-12 years age group. In giardiasis, patients presenting with acute diarrhoea stool, samples were positive in 80% (n=12/15) on first day, 13.3% (n=2/15) on second day and 6.6% (n=1/15)on third day. In patients presenting with chronic diarrhoea stool samples were positive in 76% (n=19/25)on first day, 16% (n=4/25)on second day and 8% (n=2/25) on third day. Conclusion: Giardiasis is still a common cause of acute and chronic diarrhoea. Fresh stool examination is the easiest and reliable method of diagnosing giardiasis.